1990
DOI: 10.1093/jac/26.suppl_b.181
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of pefloxacin in the treatment of typhoid fever in Algeria

Abstract: The efficacy and safety of pefloxacin 400 mg twice daily for seven days in the treatment of typhoid fever was investigated in an open, non-comparative study involving 37 patients infected with Salmonella typhi. Between day 5 and the end of treatment, all patients showed clinical improvement. The clinical cure rate at the end of the treatment period was 89.2%. One month after the end of treatment, the final assessment showed a clinical cure rate of 94.6% with relapses occurring in only two patients. Both these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Two of the patients presented 6 weeks later with possible relapses, but typing was not reported for the "relapse" strains, and one of these patients may have been reinfected. Pefloxacin given for 7 days had efficacy similar to that of ciprofloxacin (1).…”
Section: Resultsmentioning
confidence: 84%
“…Two of the patients presented 6 weeks later with possible relapses, but typing was not reported for the "relapse" strains, and one of these patients may have been reinfected. Pefloxacin given for 7 days had efficacy similar to that of ciprofloxacin (1).…”
Section: Resultsmentioning
confidence: 84%
“…A contribution on the efficacy of pefloxacin in the treatment of typhoid fever was reported in Algeria in 1990 in patients with S. Typhi, indicating that a seven-day treatment of 400 mg of this quinolone twice a day provides a good alternative to the treatment of this disease [67]. In Egypt, Girgis et al [68] reported that one gram of azithromycin orally administered once on the first day, followed by 500 mg given orally once daily for the next six days or 500 mg of ciprofloxacin orally twice daily for seven days were both clinically and bacteriologically effective against typhoid fever caused by both susceptible and MDR S. Typhi strains.…”
Section: Antimicrobial Resistance and Treatmentmentioning
confidence: 99%
“…Fluoroquinolones have been used for the treatment of enteric fever since the 1980s, and 100% cure rates were obtained with 14-to 15-day regimens of ciprofloxacin (9,11), ofloxacin (2,16), and pefloxacin (1,8), which have not been achieved with standard drugs. In addition, since quinolones are intracellularly active drugs, they may have lower relapse rates in the treatment of typhoid fever.…”
mentioning
confidence: 99%